Single nucleotide polymorphisms in the non-coding region of STIM1 gene are associated with Parkinson disease risk in Chinese Han population - Lou, Danning; Wang, Jun; Wang, Xiaohang (Medicine (Baltimore), 2020)
The stromal interaction molecule 1 (STIM1) gene contributes essentially to Ca transport, thus it is functionally related to neurodegenerative disorders. The objective of this study was to investigate the correlation between single nucleotide polymorphisms (SNP) in the non-coding region of STIM1 gene and the risk for Parkinson disease (PD) in a Chinese Han population.In a cohort composed of 300 PD patients and 300 healthy individuals from a Chinese Han population, we analyzed genotypes for five novel SNPs, rs7934581, rs3794050, rs1561876, rs3750994 and rs3750996 in the non-coding region of STIM1 gene. The levels of STIM1 protein in plasma of these subjects were also assessed by enzyme-linked immunosorbent assay (ELISA).We found that the SNPs of STIM1 gene rs7934581, rs3794050, rs1561876, and rs3750996 were associated with increased PD risk, while rs3750994 SNP was not. An increased risk of PD was observed in subjects with the TAAG and TGAG haplotypes of rs7934581, rs3794050, rs1561876, rs3750996. Moreover, PD risk was significantly elevated only in subjects with age ≥60 years or females who carry the STIM1 rs3794050 minor allele. There was a significant difference in plasma STIM1 protein levels between subjects with different genotypes of STIM1 rs7934581, rs3794050, rs1561876, and rs3750996.STIM1 gene rs7934581, rs3794050, rs1561876, rs3750996 SNPs are associated with increased PD risk, and its mechanism may be related to abnormal STIM1 gene expression.